A novel technique to hide information using Daubechies Transformation - Mandal, Jyotsna Kumar; Das, Sujit; Sengupta, Madhumita (International Journal of Computer Sciences and Engineering, 2025)
Steganography is an ancient approach of fusing data into innocence medium to hide data secretly in such a way no one can have knowledge of it. This paper presents a technique of Image steganography on frequency domain through Daubechies Transformation. This transformation converts image from spatial domain to frequency domain and allowed embedding with a payload of 2.0 bpb without visual degradation. A gray level image considered as innocent medium of size NxN, where N = 2p, p is an positive integer & is divided into 4x4 non-overlapping blocks in a row major order and a 2D Daubechies Transformation is applied to each of (NxN)/16 blocks to generate frequency components. Three layer of adjustment in terms of security enhancement are applied to improve the quality of stego image. The number of bits embedded per pixel or block is a variable and based on hash function which is used to find the position of each bit. After embedding 4 bits from LSB are grouped into two pairs and XORed, bitwise results are shuffled and stored on last four bits from LSB